Gestão do trabalho em saúde: uma análise a partir do PMAQ-AB na macrorregião Oeste do Paraná - Frigotto, Vania (2018)
The management of health work is a strategic policy in which one must effectively guarantee basic requirements for the valorization of the worker and his work, through the guarantee and structuring of career plans, salaries and ties, as well as the possibility of negotiating work relations, qualification, qualification and permanent education.The present dissertation proposes to discuss how the work management has been carried out in the basic care services of the western macroregion of Paraná, based on data presented in the National Program for Improving Access and Quality of Basic Care (PMAQ-AB). The objective is to analyze the management of work in primary health care services in the municipalities that joined the 2nd cycle of PMAQ-AB in the western macroregion of the state of Paraná. An exploratory descriptive study of documentary sources referring to the results produced in the second cycle of PMAQ-AB in the municipalities within the western macroregion of Paraná, which allowed the analysis from two approaches: training and qualification of professionals and the link and plan career, positions and salaries. The precariousness of work is inherent to capitalist society. This was evidenced also in the management of health work with the indication of diversity as 4 modalities of contraction, flexibility of 32.4% of the links, low service time, scarce existence of PCCS to 48.1%, low adherence to complementary training processes with 31.5% of physicians and 43.25% of nurses. The basic attention in the western macroregion of Paraná has been reproducing this precarious work profile resulting from the decrease in the number of statutory civil servants being replaced by outsourced employees, social security rights, insecurity in the maintenance of employment, lack of guarantees, absence of among other scarce realities that contribute to the vulnerability of the various facets of precariousne.